ANALISIS KEMAMPUAN KEUANGAN DAERAH: STUDI KASUS KOTA JAMBI DAN KABUPATEN BATANGHARI1 - Parmadi, Parmadi; Sagala, Lerinda (Jurnal Paradigma Ekonomika, 2013)
The purpose of this study is to investigate the financial capability and the level difference between Jambi City and Batanghari Regions during the period 2001-2010. Descriptive analysis methods used for qualitative and quantitative description of the two regions of research. Regional differences in the level of fiscal capacity between the two regions were tested with different test calculations with the difference of two parameters hypothesis proportions.The results obtain, first; fiscal decentralization ratio in both regions are included in the low category, and the results of the different test statistics to conclude there is a real difference of fiscal decentralization ratio between the two regions during the study period. Second; the regional fiscal centralization ratio included in the high category, but based on different test found no statistically significant difference between the two regions. Third; region funding ability ratio in both areas are included in the low category, and in both there is a real difference over the period 2001-2010Key Word: financial capability, fiscal decentralization, fiscal centralization